Production of the biomimetic small diameter blood vessels for cardiovascular tissue engineering - TOKSOY ÖNER, EBRU; OKTAR, FAİK NÜZHET; EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN (TAYLOR & FRANCIS AS, 2019)
A novel biomimetic vascular graft scaffolds were produced by electrospinning method with the most superior characteristics to be a proper biomimetic small diameter blood vessel using Polycaprolactone(PCL), Ethyl Cellulose(EC) and Collagen Type-1 were used to create the most convenient synergy of a natural and synthetic polymer to achieve similarity to native small diameter blood vessels. Scanning Electron Microscopy(SEM), Fourier Transform Infrared Spectroscopy(FTIR), Differential Scanning Calorimetry Analysis(DSC), tensile measurement tests, and in-vitro and in-vivo applications were performed. Results indicated significant properties such as having 39.33 nm minimum, 104.98 nm average fiber diameter, 3.2 MPa young modulus and 135% relative cell viability. [GRAPHICS] .
Keywords: Cardiovascular tissue engineering; collagen; electrospinning; ethyl cellulose; polycaprolactone; SCAFFOLD; PROLIFERATION; FABRICATION; NANOFIBERS; HEPARIN; PATIENT; GRAFTS